Exploring the Experiences of Parents Caring for Children with Autism Spectrum Disorder in Nepal - Thapa, Yogendra; Khatri, Bishnu Bahadur; Koirala, Kamal Prasad (International Journal of Atharva, 2024)
This study aimed to explore the experiences of parents caring for children with Autism Spectrum Disorder (ASD). Ten parents (three males, seven females) with at least seven years of ASD caregiving experience were purposively sampled. In-depth interviews, recorded with consent, were conducted and transcribed, supplemented by phone interviews. Manual analysis of the data revealed common themes and patterns, offering insights into the challenges and experiences of ASD caregiving in Nepal. Parents in Nepal invest significant time and resources into their children's well-being, but identifying atypical behavior, particularly in children with ASD, might lead to stress and complications. Challenges in effective parenting stem from cultural, economic, and knowledge gaps in ASD caregiving. While sharing culture and essential caregiving knowledge aids in stress management, it's insufficient. Local governments and community groups might be offered accessible resources. Similarly, comprehensive support networks, stress management courses, instructional materials, and targeted interventions are necessary to address family-related stress effectively.